Bullying perpetration and social status in the peer group: A meta-analysis - Wiertsema, Maria; Vrijen, Charlotte; van der Ploeg, Rozemarijn; Sentse, Miranda; Kretschmer, Tina (Journal of Adolescence, 2023)
Introduction: Associations between bullying perpetration and social status vary, not only between different facets of social status but also between bullying in primary versus secondary school. The main aim of the present study was to meta-analyse existing evidence regarding the prospective associations between bullying perpetration and various facets of social status, that is, popularity, peer acceptance, peer rejection, and social preference. Methods: Electronic databases were searched to identify studies on bullying perpetration and later social status published up to January 17, 2022. Multilevel random effects models were performed using Metafor and differences in effect sizes as a function of substantive and methodological moderators were tested. Results: In total, 116 effects were included from 18 publications, reporting on 17 different samples and more than 15,000 participants (mean age bullying assessment = 11.57 years, on average 51% female participants). Most samples were from the United States (7) or Europe (7). Overall, bullies were more popular, but also more rejected and scored lower on social preference compared with non-bullies. These associations remained when effects were adjusted for previous social status and other confounders. No link between bullying perpetration and acceptance was found. There was little evidence that effect sizes differed as a function of moderators. Conclusions: Bullies become more popular over time, but also have a higher risk of being rejected and being less socially preferred. Bullying perpetrators are more popular but also more rejected by their peers. There is no evidence that these links differ depending on sex or age at which perpetrators bully, reporter or type of bullying.
CRIS-Team Scopus Importer:2025-03-19
Keywords: bullying perpetration; meta-analysis; peer acceptance; peer rejection; popularity; social preference